Probiotics for constipation and gut microbiota in Parkinson's disease. (October 2022) - Du, Yitong; Li, Yue; Xu, Xiaojiao; Li, Rongxue; Zhang, Mingkai; Cui, Ying; Zhang, Liyan; Wei, Zheng; Wang, Shiya; Tuo, Houzhen
Abstract: Introduction: Constipation is one of the common non-motor symptoms in Parkinson's disease that significantly impacts patient quality of life. Probiotics supplementation may improve constipation symptoms, but its effect on the gut microbiota population is unclear. Methods: In this randomized controlled study, 46 PD patients with constipation according to Rome Ⅲ criteria were recruited. The number of complete bowel movements per week, degree of defecation effort, Bristol stool Scale (BSS), Patient Assessment of Constipation symptom (PAC-SYM) and Patient assessment of constipation quality of life questionnaire (PAC-QOL) were collected pre- and post-intervention to evaluate the constipation symptoms. In addition, fresh feces of subjects before and after intervention and healthy controls were collected for 16s rRNA gene V3–V4 region sequencing to compare bacterial flora differences. Results: Compared with the control group, the treatment group increased the average number of complete bowel movements per week (1.09 ± 1.24 vs. 0.04 ± 0.64, P < 0.001). Probiotics supplementation reduced the BSS score (0.65 ± 0.93 vs. −0.17 ± 0.94, P = 0.004), PAC-SYM score (4.09 ± 6.31 vs. −1.83 ± 4.14, P < 0.001), PAC-QOL score (10.65 ± 16.53 vs. 0.57 ± 12.82, P = 0.042), and degree of defecation effort score (1.00 ± 0.80 vs. 0.00 ± 0.30, P < 0.001). The improvement rate of constipation in the probiotics group was significantly higher than that in the control group (52.2% vs. 8.7%, P = 0.001). PD patients showed intestinal flora disorders compared to healthy controls. After 12 weeks of probiotics treatment, g_Christensenella_sp._Marseille-P2437 significantly increased, while g_Eubacterium_oxidoreducens_group, g_Eubacterium_hallii_group and s_Odoribacter_sp._N54.MGS-14 decreased (p < 0 0.05). Conclusions: Probiotics treatment can effectively improve the constipation symptoms of PD patients and positively affected the gut microbiota. Highlights: Gut dysbiosis have been confirmed in PD patients. After probiotics treatment, there was a significant increase in one bacterium and a decrease in three. Complex-probiotic supplementation may improve constipation in Parkinsonism. Complex-probiotics may change Gut Microbiota population against PD.